2015
DOI: 10.1515/jppr-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of segetal weed community in continuous potato cultivated with metribuzin-based weed control

Abstract: The objective of the work reported here was to determine the relationship between herbicide rate and the biodiversity of weed communities in potato cultivated in continuous cropping. A seven-year field experiment was conducted to examine the effect of 4 metribuzin rates and an uncontrol on weed infestation in successive years of continuous potato cultivation. The following indices were calculated: the Shannon-Wiener and Simpson's indices of species diversity and the Simpson's index of domination. A total of 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Application of herbicides is believed to be a factor causing floristic impoverishment of agrophytocoenoses [Pawlonka et al 2015]. In the present study, the use of herbicides significantly increased the species richness index in maize and narrow-leaved lupin as compared to mechanical weed control.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Application of herbicides is believed to be a factor causing floristic impoverishment of agrophytocoenoses [Pawlonka et al 2015]. In the present study, the use of herbicides significantly increased the species richness index in maize and narrow-leaved lupin as compared to mechanical weed control.…”
Section: Discussionsupporting
confidence: 46%
“…According to Nkoa et al [2015] three indices are often used to estimate diversity within plant communities: the Margalef index, the Shannon-Wiener diversity index, and the Simpson's dominance index. In the last decade, many papers on weeds diversity have appeared in the world literature [Feledyn-Szewczyk 2008, Jastrzębska et al 2012, Mézière et al 2015, Pawlonka et al 2015] also including those relating to the influence of intercropping system on the diversity indices of weed communities [Baumann et al 2000, Takim 2012]. However, in literature are comparatively few articles that deal with the weed diversity in strip intercropping, in particular using other indicators than the number or mass of weeds.…”
Section: Introductionmentioning
confidence: 99%
“…However, the least amount of weed biomass was observed in treatments of wheat and canola mulches and it was found that these treatments can reduce weed biomass compared to weed infested treatment by a rate of 83% and 81% decrease, and this reflects the ability of plant residues in suppressing weeds and preventing their growth as well as preventing the spread of weeds and reducing the crop yield (Duppong et al, 2004). Plant residues are not only affect the soil but also can affect the germination, survival, growth and competitive ability of weed and crop plants (Majd et al, 2014;Pawlonka et al, 2015;Azadbakht et al, 2017). Although in current study, the lowest biomass of broadleaf and grass weeds showed a significant difference with the weed infested treatment and broadleaf weeds had more biomass than grass weeds (Fig.…”
Section: Weed Biomassmentioning
confidence: 57%
“…One reason for the decline of species diversity as a result of the use of mulch, is reducing amount of light reached into weed canopy, because increasing the coverage layer of mulch, more percent of light absorbed by crops or by mulch and therefore the remaining amount of light is reduced to weeds consumption as a result of reduced weed density and diversity (Dvorak et al, 2012;Azad et al, 2015). Brassica plant debris in addition to preventing light from reaching weed seeds and prevent the germination of weed spectrum like some monocots may reduce the species diversity also Allelochemicals released by the organs of these plants (Brassicas) may be effective on weed species composition (Pawlonka et al 2015). The use of herbicides as a result of a specific range of weed control can be reduced weed diversity Nikolic et al, 2013).…”
Section: Weed Species Diversity and Densitymentioning
confidence: 99%
“…The effect in pea most likely occurred because the herbicide used did not have a comprehensive impact. In addition, eliminating some species may cause species impoverishment in general biodiversity [49] and will allow species such as C. album to establish a stable Agricultural Research & Technology: Open Access Journal seed bank and thus the ability to maintain viability in the soil [6].…”
Section: Resultsmentioning
confidence: 99%